2010
DOI: 10.1111/j.1467-8683.2010.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Securities Laws, Control of Corruption, and Corporate Liquidity: International Evidence

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: Previous studies have reported the relationship between corporate governance and corporate liquidity (cash holdings). Factors affecting corporate governance, such as securities laws and control of corruption, should have bearing on corporate liquidity and its value. This study focuses on national-level predictors of cash holdings such as securities laws and control of corruption and examines their impact on corporate liquidity, as well as its value from the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 72 publications
(213 reference statements)
6
47
0
1
Order By: Relevance
“…We also find a positive and significant relationship between the MB ratio and TSD (ρ < 0.01). The result indicates that high market growth representing the higher growth potential leads to more TSD, consistent with Chen [48]. Moreover, LEV and TSD have a negative and significant relationship (ρ < 0.10) as expected and the result is consistent with Khan et al [18], and Ntim et al [14].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We also find a positive and significant relationship between the MB ratio and TSD (ρ < 0.01). The result indicates that high market growth representing the higher growth potential leads to more TSD, consistent with Chen [48]. Moreover, LEV and TSD have a negative and significant relationship (ρ < 0.10) as expected and the result is consistent with Khan et al [18], and Ntim et al [14].…”
Section: Resultssupporting
confidence: 86%
“…MB: Market-to-Book ratio measured as a natural log of the equity's book value divided by the equity's market value following de Villiers et al [6]. The variable explains the organization's long-term growth potential and sustainability opportunities [6,48].…”
Section: Control Variablesmentioning
confidence: 99%
“…Liquidity was observed through Affä rsdata, which contains accounting data from the annual report of 2009. It could be expected to be inversely correlated with the monitoring function since high liquidity reduces short-term financial stress (Chen, 2011). Solidity, i.e., leverage measured as equity/total capital, was observed through Affä rsdata, which contains accounting data from the annual report of 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, from the perspective of a developed country, Fernández-Gago et al [10] have found that there is a negative relationship between an independent director and his or her political connections in the CSR disclosure of Spanish corporations, while Shi et al [71] have shown how high-level, politically-connected independent directors have destroyed the value of Chinese firms. According to the arguments of Shi et al [71], Muttakin et al [4], Chen [26] and Chen et al [38] we believe that in Bangladesh, which has a looser control over corruption and the rule of law, the political connection of firms has drastically reduced the role of legal experts. As a result, we propose the following hypothesis:…”
Section: The Influence Of Interaction Effects Between Political Direcmentioning
confidence: 97%
“…As corruption is a global problem that compromises governance, transparency and accountability, it is treated as a cancerous presence within society [20]. Moreover, the existing literature also reports that developing countries are highly affected by corruption, because it affects both economic growth and financial stability [20][21][22][23][24][25][26]. This raises the question of why researchers covering developing countries have neglected the issue of corporate corruption.…”
Section: Introductionmentioning
confidence: 99%